Evaluation of Comorbidity Indices for a Study of Patient Outcomes Following Cervical Decompression Surgery: A Retrospective Cohort Study. Issue 24 (December 2015) - Oichi, Takeshi; Oshima, Yasushi; Takeshita, Katsushi; Chikuda, Hirotaka; Tanaka, Sakae
Abstract : Study Design: Retrospective cohort study. Objective: The objective of this study was to investigate the predictive validity of 2 comorbidity indices in a study of patient outcomes following cervical decompression surgery. The comorbidity indices evaluated were the Charlson comorbidity index (CCI) and the self-administered comorbidity questionnaire (SCQ). Summary of Background Data: Comorbidities have been shown to have independent prognostic factors for HRQOL outcome in patients with spinal disorders. However, no appropriate evaluation method of comorbidity has been established in spinal research. Methods: We retrospectively reviewed 86 cervical myelopathy cases treated by decompression surgery between 2004 and 2010. Health-related quality of life (HRQOL) outcomes were measured using the short form 36 physical component summary (PCS) and the neck disability index (NDI), administered both pre- and postoperatively. Patient comorbidity was evaluated by the CCI and SCQ. The CCI was calculated by the medical record review, whereas the SCQ was obtained from patients' self-reports. The correlations between HRQOL outcomes and comorbidity indices were investigated. Thereafter, multiple liner regression analyses were performed to assess the performance of these comorbidity indices for predicting postoperative HRQOL. Results: The SCQ significantly correlated with both pre- and postoperative PCS scores and both pre- and postoperative NDI scores. The CCI did not correlate significantly with any outcome measure. On regression analysis, the CCI was a poor predictor of postoperative HRQOL, demonstrating only 0.2% of variance in the PCS score ( P  = 0.25) and only 0.4% of variance in the NDI score ( P  = 0.59). In comparison, the SCQ was a significant predictor of postoperative HRQOL, demonstrating 4.0% of variance in PCS score ( P  = 0.011) and 10.2% of variance in NDI score ( P  = 0.0001). Conclusion: The SCQ, but not the CCI, was a robust predictor of postoperative HRQOL. Our study suggests that the SCQ score is a more appropriate adjustment for HRQOL outcomes following cervical decompression surgery. Level of Evidence: 3